2020
DOI: 10.1038/s41419-020-2361-z
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cancer stem cell properties, angiogenesis, and vasculogenic mimicry by miR-450a-5p/SOX2 axis in colorectal cancer

Abstract: Growing evidence indicates that a small number of cancer cells express stem cell markers and possess stem cell-like properties that promote malignant progression. Sex-determining region Y-box2 (SOX2) is a stem cell transcription factor essential for maintaining the properties of cancer stem cell (CSC). As CSC properties have been associated with angiogenesis and vasculogenic mimicry (VM), we aimed to comprehensively investigate whether SOX2 regulates CSC properties, angiogenesis, and VM in colorectal carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 36 publications
4
32
0
Order By: Relevance
“…Cell vasculogenic mimicry was calculated via three‐dimensional assay as reported previously 28 . Different concentrations of Sal‐A (0–50 µmol/L) were treated with NSCLC cells for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Cell vasculogenic mimicry was calculated via three‐dimensional assay as reported previously 28 . Different concentrations of Sal‐A (0–50 µmol/L) were treated with NSCLC cells for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Sex-determining region Y-box2 (SOX2), a master regulator of embryonic and induced pluripotent stem cells (iPSCs), drives cancer stemness, fuels tumor initiation, and contributes to tumor aggressiveness 4 . In our recent study, we found that SOX2 promotes chemoresistance, confers CSCs properties, and promotes epithelial–mesenchymal transition (EMT) in colorectal cancer (CRC) 5 . However, the underlying mechanism of this phenomenon is not well-characterized.…”
Section: Introductionmentioning
confidence: 99%
“…2). Among JICD1-upregulated DEGs, SOX2 plays a pivotal role in the maintenance of embryonic and neural stem cells and is associated with cancer progression in numerous solid tumors 29,30,31 . To confirm the oncogenic function of SOX2, we established SOX2-overexpressing cells (Supplementary Fig.…”
Section: Jicd1 Exerts Oncogenic Functions By Regulating Sox2 Expressionmentioning
confidence: 99%